LEGAL ANALYSIS OF CHILDREN'S RIGHTS FROM SIRI MARRIAGES (CASE STUDY IN BATAM CITY) - Fitri Sembiring Milala; Ali Amran; Maniah (CV. RADJA PUBLIKA, 2025)
Unregistered marriages are still a common phenomenon in Batam City, causing serious impacts on the status and legal protection of children. Because these marriages are not recognized, children lose their basic rights such as identity, financial support, inheritance, and proper education. This problem is not only individual in nature, but has become a widespread social issue, exacerbated by the high population dynamics in Batam, which are characterized by urbanization, population mobility, and cultural heterogeneity, all of which influence marriage practices in society.This study aims to analyze the legal arrangements for children from unregistered marriages according to Indonesian positive law, the implementation of the rights of children from unregistered marriages in Batam City, and to identify relevant obstacles and solutions. The research focuses on how existing regulations, such as Constitutional Court Decision No. 46/PUU-VIII/2010 and the Child Protection Law, are applied in the field and the challenges faced in ensuring the fulfillment of these children's rights. The research method used is a normative and empirical juridical approach. Data was obtained through an in-depth literature study of legislation and legal doctrine, as well as direct interviews with key informants such as judges from the Religious Court and District Court, the Head of Civil Registration Services at the Batam City Population and Civil Registration Office, and couples who had entered into unregistered marriages. This approach allowed for a comprehensive analysis of the applicable legal norms and the social reality in the field. The research results suggest that the Batam City Government and related agencies should strengthen the protection of children born from unofficial marriages through clear regional policies, administrative sanctions, and simple child recognition procedures. The implementation of children's rights needs to be strengthened through legal socialization, integrated services, community leader involvement, and outreach programs in areas with low registration rates to ensure that every child receives proper recognition and protection.